Meningkatkan Kemampuan Berlari, Melempar, dan Menangkap Bola Melalui Permainan Tic Tac Toe Ball di Sekolah Dasar - Irvan Nur Nugroho (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
The learning outcomes of fourth grade students of SDN Karangtengah III for the 2019/2020 academic year, the material for small ball games (kasti) including the basic movements of running, throwing and catching the ball is still low. The results showed an increase in learning outcomes of the basic motion of running, throwing and catching the ball after using the tic tac toe ball game. The result of the improvement is that through the tic tac toe ball game, students who get learning outcomes meet the minimum completeness criteria for grade IV is 77, in the initial condition there are only six children or about 26%. After the implementation of learning using the tic tac toe ball game, students who succeeded in achieving the minimum completeness criteria 77 increased to 21 students or about 91%. The conclusion of this research is that the tic tac toe ball game can improve the learning outcomes of the basic movements of running, throwing, and catching the ball for fourth grade students of SDN Karangtengah III in the 2019/2020 academic year.